Interaktiver Wissensaustausch – ein Ansatz zur nachhaltigen Implementierung evidenzbasierter Programme in der sportwissenschaftlichen Gesundheitsförderungsforschung - Rütten, Alfred; Frahsa, Annika; Gelius, Peter; Schätzlein, Valentin (22.Dvs-Hochschultag, 2015)

Sind Präventionsmaßnahmen zur Bewegungsförderung kosteneffektiv? Ein systematischer Review... - Rütten, Alfred; Abu-Omar, Karim; Burlacu, Ionut; Schätzlein, Valentin; Suhrcke, Marc (Gesundheitswesen, 2017)

The cost-effectiveness of physical activity interventions: A systematic review of reviews - Abu-Omar, Karim; Rütten, Alfred; Burlacu, Ionut; Schätzlein, Valentin; Messing, Sven; Suhrcke, Marc (Preventive Medicine Reports, 2017)

Toward the economic evaluation of participatory approaches in health promotion: lessons from four German physical activity promotion projects - Gelius, Peter; Sommer, Raluca; Abu-Omar, Karim; Schätzlein, Valentin; Suhrcke, Marc (Health promotion international, 2021)
Health promotion increasingly employs participatory approaches, but the question arises whether the likely higher costs of participation also translate into greater benefits. This article takes a first step toward a full health economic evaluation by comprehensively reporting the costs of a specific participatory approach, Cooperative Planning, in a German research consortium to promote physical activity. We conducted a costing analysis of Cooperative Planning at 22 sites across six settings. Project teams used a custom template to record resource use. We calculated average costs per meeting, site and setting using the opportunity costs approach, and obtained feedback from participating researchers. A total of 144 planning meetings with an average of nine participants were conducted. Costs per meeting varied significantly across settings. Differences were mostly attributable to varying meeting duration, preparation time and numbers of participants. Across settings, human resources accounted for roughly 95% of the costs. Implementing researchers reported challenges regarding the logic and methods of the health economic analysis. A participatory approach to physical activity promotion may cause substantially varying costs in different settings despite similar cost structures. However, their value for money could turn out comparably favorable if (and only if) the expected benefits is indeed forthcoming. Despite some challenges implementing the costing exercise into the logistics of ongoing participatory projects, this analysis may pave the way toward a full health economic evaluation, and the template may be useful to future participatory health promotion projects.
CRIS-Team WoS Importer:2022-04-01